The clinical fabrication of polyolefin mouthguards formed over fixed orthodontic appliances - Westerman Bill; Kerr Michael; Tod Marcus (Sciendo, 2021)
Using a new polyolefin material without impressions and models, fifty-two mouthguards were fabricated at chairside by a dental professional. Patient acceptance, operator assessment, mouthguard retention and fabrication time were assessed. The study demonstrated the practicality of custom-made mouthguard fabrication over fixed orthodontic appliances and recommends the procedure as a useful adjunct to orthodontic practice.